Coexistent Hyperuricemia and Gout in Rheumatoid Arthritis: Associations With Comorbidities, Disease Activity, and Mortality. Issue 7 (7th June 2020) - Chiou, Andrew; England, Bryant R.; Sayles, Harlan; Thiele, Geoffrey M.; Duryee, Michael J.; Baker, Joshua F.; Singh, Namrata; Cannon, Grant W.; Kerr, Gail S.; Reimold, Andreas; Gaffo, Angelo; Mikuls, Ted R.
Abstract : Objective: Although hyperuricemia and gout can complicate the course of rheumatoid arthritis (RA), the impact of these factors on outcomes in RA is unclear. We undertook this study to examine associations of coexistent hyperuricemia and gout with RA disease measures, RA treatments, and survival. Methods: Participants from a longitudinal RA study were categorized by the presence of gout and serum urate (UA) status. Groups were compared by baseline patient characteristics, RA disease activity, treatments, and comorbidities. Associations of baseline serum UA levels with all‐cause and cardiovascular disease (CVD)–related mortality were examined in multivariable survival analyses. Results: Of 1, 999 participants with RA, 341 (17%) had serum UA concentrations of >6.8 mg/dl, and 121 (6.1%) were diagnosed with gout. There were no significant associations of serum UA concentration or gout with RA disease activity or treatment at enrollment, with the exception that those with gout were more likely to be receiving sulfasalazine and less likely to be receiving nonsteroidal antiinflammatory drugs. After adjustments for age and sex, moderate hyperuricemia (serum UA >6.8 to ≤8 mg/dl) was associated with an increased risk of CVD‐related mortality (hazard ratio 1.56 [95% confidence interval 1.11–2.21]). This association was attenuated and not significant following additional adjustment for comorbidities that more commonly accompany hyperuricemia. Results corresponding with serum UA concentrations of >8.0 mg/dl were similar, although not reaching statistical significance in any model. There were no associations of baseline serum UA concentration with all‐cause mortality. Conclusion: Our study reports the frequency of hyperuricemia and gout in patients with RA. These results demonstrate strong associations of hyperuricemia with CVD mortality in this population, a risk that appears to be driven by excess comorbidity.